Application of speed and agility training: How do they affect dribbling skills in football? - Chafidz, Reyhan; Juli, Candra; Troyanovska, Mariya; ‘Ala, Faridatul (Universitas Tanjungpura, 2023)
Background and Study Aim. Dribbling skills have a crucial role in the achievement of a football player, especially at a young age level such as the SSB Medan Satria U-16 Football team. This study aims to investigate the effect of speed and agility on the dribbling skills of SSB U-16 Medan Satria students.Material and Methods. The method used in this research is experimental, the data collection techniques used are tests and measurements. The population in this study were SSB U-16 Medan Satria students. The sample taken from the results of purposive sampling amounted to 20 students. The instrument used is a dribbling skill test. Data analysis using the SPSS 26 application.Results. The results showed a significance value of 0.000 <0.05 so there is a significant effect of speed training on dribbling skills of soccer games. The application of agility training shows a significance value of 0.000 <0.05 so that there is a significant effect of agility training on dribbling skills of soccer games. Further results show the comparison between speed training and agility training shows a significance value of 0.000 <0.05 which means that there is a significant difference between speed training and agility training, the results also provide information that speed training is better for improving dribbling skills.Conclusions.The results of this study are expected to provide a clear picture of the effect of speed and agility training on dribbling skills at the youth level. These findings can then be applied in the development of a more specific and focused training program, with the aim of improving the quality of each player's dribbling skills.